The concept of “democratic man” in Plato, Tocqueville and Nietzsche - Vernazza, Diego (Nómadas. Critical Journal of Social and Juridical Science, 2013)
There are multiple, if not endless ways to deal with the political problem. In this article we explore a particular possibility, the anthropological one. In this approach, the question of common life is articulated around the characterization of the type of man, of human being, which corresponds to a series of laws and customs, ideas and feelings. We will examine three paradigmatic cases of this tradition –Plato, Tocqueville and Nietzsche– as all three embody a type of moral and political philosophy that is explicitly constituted as a critical diagnosis of a key moment of democratization: the Athens of V-IV century BC and the Europe of nineteenth century. Plato, Tocqueville and Nietzsche all developed their philosophy through a rather open conflict with the ideas and feelings carried by the democratic man, whose advent was considered inevitable, as part of a cycle of regimes in Plato’s case, and within the framework of a philosophy of history when looking at Nietzsche and Tocqueville.